1995
DOI: 10.1016/0370-2693(95)00214-6
|View full text |Cite
|
Sign up to set email alerts
|

Particle physics models, topological defects and electroweak baryogenesis

Abstract: We demonstrate the viability of electroweak baryogenesis scenarios in which the necessary departure from equilibrium is realized by the evolution of a network of topological defects. We consider several effective models of TeV physics, each addressing a fundamental particle physics problem, and in which the conditions necessary for defect-mediated electroweak baryogenesis are naturally satisfied. In each case we compare the strength of the model with that expected from scenarios in which baryogenesis proceeds … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…When defects are produced at the TeV scale, a detailed analysis of the dynamics of a network of these objects shows that a significant baryon-to-entropy ratio can be generated (61)(62)(63)(64)(65)(66) if the electroweak symmetry is restored around such a higher scale ordinary defect (67)(68)(69). Although a recent analysis has shown that baryonnumber violation is highly inefficient along nonsuperconducting strings (70) there remain viable scenarios involving other ordinary defects, superconducting strings, or defects carrying baryon number (71, 72).…”
Section: Defect-mediated Baryogenesismentioning
confidence: 99%
“…When defects are produced at the TeV scale, a detailed analysis of the dynamics of a network of these objects shows that a significant baryon-to-entropy ratio can be generated (61)(62)(63)(64)(65)(66) if the electroweak symmetry is restored around such a higher scale ordinary defect (67)(68)(69). Although a recent analysis has shown that baryonnumber violation is highly inefficient along nonsuperconducting strings (70) there remain viable scenarios involving other ordinary defects, superconducting strings, or defects carrying baryon number (71, 72).…”
Section: Defect-mediated Baryogenesismentioning
confidence: 99%
“…A set of model independent defect induced scenarios was also proposed [31,32]. Recent numerical work [33] shows that of these the string mediated mechanism is not efficient enough at B-asymmetry production.…”
Section: Other Approachesmentioning
confidence: 99%
“…Supersymmetric extensions of the standard model have been proposed which attempt to resolve the µ problem of the minimal supersymmetric standard model (MSSM) and the cosmological solar neutrino problem and which have strings [20]. Both these models were considered recently [21] in the context of electroweak baryogenesis from cosmic strings. Top color models [14] are another class of models where a U(1) gauge group is broken close to the electroweak scale.…”
Section: Cosmic Strings and Baryogenesismentioning
confidence: 99%